Baron, N. S. (2023). Who Wrote This? How AI and the Lure of Efficiency Threaten Human Writing. Stanford University Press / Tenen, D. Y. (2024). Literary Theory for Robots. How AI Learned to Write. Norton Shorts - Samuels, Boba (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
Two recently published books present perspectives on the impact of generative Artificial Intelligence on writing. Baron’s book attempts to discuss the question of how we might maintain distinctions between the writing done by humans versus that done by genAI, while Tenen’s book takes a historical view of the use of technologies in writing and what that implies for writers currently.